In vitro estimation of ruminal protein degradability of forages - I.E.O. Abdelgadir; R.C. Cochran; E.S. Vanzant; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1996)
Ruminal degradation of alfalfa and prairie hay protein was estimated using a proteolytic enzyme from Streptomyces griseus with or without pretreatment with cellulase or a broad spectrum carbohydrase (driselase). Estimates of the undegradable intake protein (UIP) as a percentage of total protein derived from the protease alone were higher than that measured in the animal (i.e., in vivo). Pretreatment of hay samples with cellulase (48 h incubation) or driselase improved the accuracy of UIP predictions compared with those determined using the protease alone.
Keywords: Cattlemen& #x27; s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Protein degradability; Cellulase; Driselase; Forage